2009
DOI: 10.1007/s11033-009-9751-8
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel vimentin promoter and mRNA isoform

Abstract: Cell differentiation programs require dynamic regulation of gene expression. During meiotic prophase in Saccharomyces cerevisiae, expression of the kinetochore complex subunit Ndc80 is downregulated by a 5' extended long undecoded NDC80 transcript isoform. Here we demonstrate a transcriptional interference mechanism that is responsible for inhibiting expression of the coding NDC80 mRNA isoform. Transcription from a distal NDC80 promoter directs Set1-dependent histone H3K4 dimethylation and Set2-dependent H3K36… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 36 publications
2
10
0
Order By: Relevance
“…A clear difference in the HP1α gene H3‐K36 trimethylation level was observed between MDA‐MB‐231 and MCF‐7 cells with more H3‐K36 trimethylation present in MCF‐7 cells. The H3‐K36 trimethylation profiles are in accordance with observations of other genes showing correspondence between mRNA levels and the H3‐K36 trimethylation profile [35]. ChIP analysis showed that RNA pol‐II was present throughout the HP1α gene to lesser extend in MDA‐MB‐231 cells compared with MCF‐7 cells.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…A clear difference in the HP1α gene H3‐K36 trimethylation level was observed between MDA‐MB‐231 and MCF‐7 cells with more H3‐K36 trimethylation present in MCF‐7 cells. The H3‐K36 trimethylation profiles are in accordance with observations of other genes showing correspondence between mRNA levels and the H3‐K36 trimethylation profile [35]. ChIP analysis showed that RNA pol‐II was present throughout the HP1α gene to lesser extend in MDA‐MB‐231 cells compared with MCF‐7 cells.…”
Section: Discussionsupporting
confidence: 85%
“…ChIP analyses were done essential as previously described [35]. In summary, ChIP was performed with 10 mL cultures fixed with 1% formaldehyde for 10 min followed by addition of glycine to 0.25 mM final concentration.…”
Section: Methodsmentioning
confidence: 99%
“…4C). Of those, 24 were identified as isoforms of the protein vimentin (VIM), previously described as being expressed as different isoforms due to alternative splicing [25] or different phosphorylation states of the protein [26]. The majority of the VIM isoforms (n = 19) show a lower content in P7 compared to P3 (Table 1, Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Keratin, vimentin, desmin, lamin, peripherin and GFAP are all alternatively spliced (Landon et al, 1989;Langbein et al, 2010;Lin and Worman, 1993;Park et al, 2000;Zhou et al, 2010). There are multiple splice variants of GFAP, including , , , ,  and  (Blechingberg et al, 2007; Condorelli et al, 1999; Feinstein et al, 1992;Nielsen et al, 2002;Zelenika et al, 1995) among others.…”
Section: Regulation Of If Interactions and Assembly By Alternative Spmentioning
confidence: 99%